Experimental performance of a direct evaporative cooler operating during summer in a Brazilian city - Camargo, JR; Ebinuma, C. D.; Silveira, J. L. (Elsevier B.V., 2005)
This paper presents the basic principles of the evaporative cooling process for human thermal comfort, the principles of operation for the direct evaporative cooling system and the mathematical development of the equations of thermal exchanges, allowing the determination of the effectiveness of saturation. It also presents the results of experimental tests in a direct evaporative cooler that take place in the Air Conditioning Laboratory at the University of Taubate Mechanical Engineering Department, and the experimental results are used to determinate the convective heat transfer co-efficient and to compare with the mathematical model. (c) 2005 Elsevier Ltd and IIR. All rights reserved.
Keywords: Brazil; experiment; air conditioning; evaporative system